Correlated evolution of wing morphology and echolocation calls in bats - Zou, Wenyu; Liang, Haiying; Wu, Pan; Luo, Bo; Zhou, Daying; Liu, Wenqin; Wu, Jiashu; Fang, Linjie; Lei, Yudie; Feng, Jiang (Frontiers in Ecology and Evolution, 2022)
Flight and echolocation are two crucial behaviors associated with niche expansion in bats. Previous researches have attempted to explain the interspecific divergence in flight morphology and echolocation vocalizations in some bat groups from the perspective of foraging ecology. However, the relationship between wing morphology and echolocation vocalizations of bats remains obscure, especially in a phylogenetic context. Here, we aimed to assess the correlated evolution of wing morphology and echolocation calls in bats within a phylogenetic comparative framework. We integrated the information on search-phrase echolocation call duration, peak frequency, relative wing loading, aspect ratio, and foraging guilds for 152 bat species belonging to 15 families. We quantified the association among wing morphology, echolocation call parameters, and foraging guilds using phylogeny-based comparative analyses. Our analyses revealed that wing morphology and echolocation call parameters depended on families and exhibited a marked phylogenetic signal. Peak frequency was negatively correlated with relative wing loading and aspect ratio across all bats studied. Call duration was positively correlated with relative wing loading and aspect ratio among open-space aerial foragers, edge-space aerial foragers, edge-space trawling foragers, and narrow-space gleaning foragers. Wing morphology, call duration, and peak frequency were predicted by foraging guilds. These results demonstrate that adaptive response to foraging ecology has shaped the correlated evolution between flight morphology and echolocation calls in bats. Our findings expand the current knowledge regarding the link between morphology and vocalizations within the order Chiroptera.